Salivary and plasma inflammatory mediators and secretory status in preterm delivery women with periodontitis – a cross sectional study - Nikolić, Ljubinka; Čakić, Saša; Perunović, Neda; Čolak, Emina; Kotur-Stevuljević, Jelena; Janković, Saša; Djurić, Milanko; Plećaš, Darko (Vojnosanitetski pregled, 2021)
Bacground/Aim. Preterm birth is defined as a delivery prior to the completed 37th week of gestation. Literature data suggested that periodontal processes may influence to the feto-placental unit and induce preterm delivery. The degree of the periodontal disease is influenced by secretor status. Pro-inflammatory cytokines are involved in periodontitis as well as in delivery. The combined influence of these factors on the risk of preterm birth has not been explored. The aim of our study was to investigate the associations between periodontal diseases, secretor status, and interleukin-1-β (IL1-ß) and prostaglandine E2 (PGE2) levels in women delivered preterm. Methods. The study included 56 preterm delivery women and 56 women delivered at term as a control group, aged between 17 and 41 years. Periodontal examination, blood and saliva sampling were performed within 48 hours following delivery. Secretor phenotype was determined by hemagglutination inhibition method. The concentrations of IL1-ß and PGE2 were measured by high sensitivity Enzyme-linked Immunosorbent Assay (ELISA). Results. In the pre-term birth group there were 66.1% of women with periodontitis, while in the control one there were 12.5% (p < 0.01). Concentrations of IL1-ß and PGE2 in plasma were significantly higher in the non-secretor group of women who gave birth pre-term and had periodontitis comparing to other groups. There was a significant correlation between salivary and plasma levels of PGE2 and IL1-ß in the preterm birth group (R = 0.416, p = 0.017 and R = -0.592, p < 0.001, respectively). There were no such correlations in women who delivered at term. Conclusion. Our results support the hypothesis that non-secretor phenotype and periodontitis are at least in part responsible for pathogenesis of preterm birth. This probability of negative impact of non-secretor status cannot be ignored. These findings support the need for additional research into the biology of human parturition.